h - Perry, Bob.; Lowrie, Tom.; Logan, Tracy; MacDonald, Amy.; Greenlees, Jane.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This is the eighth edition of the four-yearly review of mathematics education research in Australasia. Commissioned by the Mathematics Education Research Group of Australasia (MERGA), this review critiques the most current Australasian research in mathematics education in the four years from 2008-2011. The main objective of this review is to celebrate and recognise significant findings; highlight relationships between research; identify themes; and forecast further research directions. This theme-based review has produced a comprehensive analysis of Australasian research in a politically challenging time$1 (Bproducing a manuscript with implications for a wider, international, audience. As the 2009 Felix Klein medal winner Gilah Leder states: A substantial body of research is captured in the chapters of this review. It encompasses the labours of a community of active researchers, with varied interests and diverse theoretical perspectives. Some of the issues explored in the period covered by this volume clearly resonate with questions and concerns particularly pertinent to the changing educational environment; others are more aptly described as continuing or renewed explorations of areas of long standing concern.s
Keywords: Education; Education; Education (general).